Field reports form for submitting seasonal observations of Iowa birds, fall 1999, Jim Fuller - Fuller, James L.et al (1999)
An annotated list of birds sighted by Jim Fuller. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed